Effects of cholecalciferol supplementation on serum and urinary vitamin D metabolites and binding protein in HIV-infected youth. Issue 168 (April 2017) - Eckard, Allison Ross; Thierry-Palmer, Myrtle; Silvestrov, Natalia; Rosebush, Julia C.; O'Riordan, Mary Ann; Daniels, Julie E.; Uribe-Leitz, Monika; Labbato, Danielle; Ruff, Joshua H.; Singh, Ravinder J.; Tangpricha, Vin; McComsey, Grace A.
Highlights: Cholecalciferol supplementation effectively raises serum 25-hydroxyvitamin D in the majority of HIV-infected youth. Changes in vitamin D metabolites are similar between HIV-infected youth and controls with cholecalciferol supplementation. High-dose cholecalciferol raises 25-hydroxyvitamin D in HIV-infected youth regardless of efavirenz use. Abstract: Vitamin D insufficiency is widespread in HIV-infected patients. HIV and/or antiretroviral therapy (ART), particularly efavirenz (EFV), may interfere with vitamin D metabolism. However, few data from randomized, controlled trials exist. Here, we investigate changes in vitamin D metabolites and binding protein (VDBP) after 6 months of supplementation in a randomized, active-control, double-blind trial investigating 2 different monthly cholecalciferol (vitamin D3 ) doses [60, 000 (medium) or 120, 000 (high) IU/month] vs. a control arm of 18, 000 IU/month in 8–25 year old HIV-infected youth on ART with HIV-1 RNA <1000 copies/mL and baseline 25-hydroxycholecalciferol (25(OH)D3 ) ≤30 ng/mL. A matched healthy uninfected group was enrolled in a similar parallel study for comparison. Changes after 6 months were analyzed as intent-to-treat within/between groups [control group (low dose) vs. combined supplementation doses (medium + high)]. At 6 months, 55% vs. 82% of subjects in control and supplementation groups, respectively, reached 25(OH)D3 ≥30 ng/mL (P = 0.01) with no difference between medium and high doses (both 82% ≥30 ng/mL). There were few differences for those on EFV vs. no-EFV, except serum VDBP decreased in EFV-treated subjects (both within- and between-groups P ≤ 0.01). There were no significant differences between the HIV-infected vs. healthy uninfected groups. The major finding of the present study is that cholecalciferol supplementation (60, 000 or 120, 000 IU/month) effectively raises serum 25(OH)D3 in the majority of HIV-infected subjects, regardless of EFV use. Notably, response to supplementation was similar to that of uninfected subjects.